2013
DOI: 10.1039/c3nr01080e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of non-segregation graphene growth on Ni via isotope-labeled alcohol catalytic chemical vapor deposition

Abstract: Here we present CVD growth of graphene on Ni and investigate the growth mechanism using isotopically labeled (13)C-ethanol as the precursor. Results show that during low-pressure alcohol catalytic CVD (LP-ACCVD), a growth time of less than 30 s yields graphene films with high surface coverage (>80%). Moreover, when isotopically labeled ethanol precursors were sequentially introduced, Raman mapping revealed that both (12)C and (13)C graphene flakes exist. This shows that even at high temperature (∼900 °C) the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…This result reveals the latter assumption, nucleation on high carbon solubility catalyst occurred the same process as that on low carbon solubility catalyst, is correct. It is also consistent with the result obtained by in-situ Raman spectroscopy [4]. However, it should be noted that multilayer graphene was formed on Co and Ni, which also suggests the solid-solution and surface segregation process occurred as well.…”
Section: Resultssupporting
confidence: 91%
“…This result reveals the latter assumption, nucleation on high carbon solubility catalyst occurred the same process as that on low carbon solubility catalyst, is correct. It is also consistent with the result obtained by in-situ Raman spectroscopy [4]. However, it should be noted that multilayer graphene was formed on Co and Ni, which also suggests the solid-solution and surface segregation process occurred as well.…”
Section: Resultssupporting
confidence: 91%
“…Note that previous reports showed that the Raman spectrum of twisted bi-layer graphene (BLG) could also have a strong 2D-band [15], so the 2D/G ratio is not definitive evidence for the existence of SLG. However, there is a very strong contrast between SLG and BLG on Si/SiO 2 substrates when observed with an optical microscope, and recent studies have shown that a small blue-shift can be observed in the Raman feature of BLG compared with that of SLG [15,16]. Since there is often a multi-layer core at the center of each flake, we examined the BLG areas with Raman scattering (inset in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Such a possibility is implied by the recent progress on chemical vapor deposition of graphene which shows the presence of co-existing Raman G-band peaks corresponding to independent 12 C-and 13 C-graphene regions. [39] There have been some theoretical works on isotopic graphene superlattices. Ouyang et al studied the thermal transport properties of isotopic-superlattice graphene nanoribbons with zigzag edge using non-equilibrium Green's function method and found that the thermal conductivity of graphene nanoribbon can be reduced significantly by isotopic superlattice modulation.…”
Section: Introductionmentioning
confidence: 99%